Conductive adhesive film, method for joining dissimilar materials, semiconductor device structure, and diced chip joining film

CN122996881APending Publication Date: 2026-10-27FURUKAWA ELECTRIC CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202580023014.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-28
Filing Date
2025-03-26
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

但是,如果对半导体器件结构体进行加压处理,则存在有时在大容量功率半导体上产生裂纹等损伤的问题

Benefits of technology

根据本发明的导电性粘接膜的方式,通过具备由穿孔金属箔构成的应力缓和层,所述穿孔金属箔在利用选自由铜(Cu)、铜(Cu)合金、铝(Al)和铝(Al)合金组成的组中的至少一种金属形成的金属箔的主表面上设置有贯通孔,因此,热传导性和导电性优异,并且由于穿孔金属箔具有应力缓和特性和柔软性,即使半导体器件与搭载半导体器件的部件的热膨胀率不同,也能够抑制热疲劳和应力的蓄积,防止搭载有半导体器件的半导体器件结构体的损伤。另外,根据本发明的导电性粘接膜的方式,通过具备包含铜(Cu)、锡(Sn)、双马来酰亚胺树脂、以及上述通式(1)表示的有机膦和/或上述通式(2)表示的有机硫化物的第一粘接层和第二粘接层,能够在不使用昂贵的贵金属的情况下得到耐热疲劳性、烧结容易性、空隙防止性优异的导电性粘接膜。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122996881A_ABST
    Figure CN122996881A_ABST
Patent Text Reader

Abstract

The present invention relates to a conductive adhesive film (10) for joining a semiconductor device and a member, comprising: a stress relaxation layer (1) composed of a perforated metal foil provided with through-holes on a main surface of a metal foil formed of at least one metal selected from the group consisting of copper (Cu), a copper (Cu) alloy, aluminum (Al), and an aluminum (Al) alloy; a first adhesive layer (2) provided on a side of the stress relaxation layer (1) for joining a semiconductor device, containing copper (Cu), tin (Sn), a bismaleimide resin, and an organic phosphine and / or an organic sulfide; and a second adhesive layer (3) provided on a side of the stress relaxation layer (1) opposite to the side for joining the semiconductor device, containing copper (Cu), tin (Sn), a bismaleimide resin, and an organic phosphine and / or an organic sulfide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to conductive adhesive films for bonding semiconductor devices to components such as substrates or lead frames, bonding methods for dissimilar materials using conductive adhesive films, semiconductor device structures having conductive adhesive films, and dicing die-bonding films having conductive adhesive films. Background Technology

[0002] In recent years, high-capacity power semiconductors, represented by SiC, have been widely used for purposes such as reducing power consumption. Because of their wider bandgap than traditional silicon, high-capacity power semiconductors like SiC have a wider operating temperature range and can be used at higher current densities. Therefore, devices incorporating high-capacity power semiconductors, such as motor inverters, can simultaneously achieve high performance and miniaturization.

[0003] However, although high-capacity power semiconductors maintain switching performance even at high current densities and associated high operating temperatures (junction temperatures), when high-capacity power semiconductors are repeatedly subjected to high operating temperatures, the surrounding mounting components, especially lead-free solder used in surface mount sections, suffer thermal fatigue due to repeated exposure to high and low temperatures, which can lead to the failure of devices with high-capacity power semiconductors.

[0004] Therefore, a solution has been proposed to use silver-based sintering materials as the mounting materials for high-capacity power semiconductors. For example, a semiconductor device bonding component (Patent Document 1) has been proposed, which includes: a heat stress relief layer composed of any one of silver, copper, gold and aluminum; a first silver solder layer disposed on the side of the heat stress relief layer that bonds to the semiconductor device, and mainly composed of silver and tin; and a second silver solder layer disposed on the side of the heat stress relief layer that bonds to the substrate, and mainly composed of silver and tin.

[0005] However, in silver-based sintered materials such as Patent Document 1, if a bond is to be obtained that can withstand repeated high-temperature operation and has excellent reliability and thermal fatigue resistance, it is necessary to sinter at extremely high pressure under high temperature conditions above 300°C. Since silver is expensive and the sintering process is difficult, there are significant problems in terms of practicality.

[0006] Furthermore, in the adhesive layer of Patent Document 1, which is composed of a silver solder layer with silver and tin as the main components, an oxide coating forms on the silver and tin. When power semiconductors are bonded to components such as substrates or lead frames by transient liquid phase sintering (TLPS), the aforementioned oxide coating hinders the TLPS reaction. Therefore, an investigation was conducted on reducing the aforementioned oxide coating by adding an alcohol-based or acid-based flux (reducing agent) to the adhesive layer with silver and tin as the main components, thereby preventing the formation of the aforementioned oxide coating.

[0007] However, alcohol- or acid-based fluxes generate water molecules during the reduction of the aforementioned oxide coating, leading to voids in the sintered adhesive layer. Therefore, when using alcohol- or acid-based fluxes, pressure treatment is required on the semiconductor device structure with high-capacity power semiconductors mounted on a substrate or similar surface to eliminate these voids. However, pressure treatment of the semiconductor device structure can sometimes cause damage such as cracks in the high-capacity power semiconductors.

[0008] (Existing technical literature) (Patent Documents) Patent Document 1: Japanese Patent Application Publication No. 2022-50871 Summary of the Invention

[0009] The problem that the invention aims to solve The present invention was made in view of the above circumstances, and its object is to provide a conductive adhesive film that does not use expensive precious metals and has excellent thermal fatigue resistance, sintering ease and void prevention, a bonding method for dissimilar materials using the above-mentioned conductive adhesive film, a semiconductor device structure having the above-mentioned conductive adhesive film, and a die-cutting bonding film having the above-mentioned conductive adhesive film.

[0010] Technical means for solving problems The essential elements of this invention are as follows.

[0011] [1] A conductive adhesive film for bonding semiconductor devices and components, comprising: A stress-relieving layer is composed of a perforated metal foil, wherein the perforated metal foil has through holes on the main surface of the metal foil formed using at least one metal selected from the group consisting of copper (Cu), copper (Cu) alloys, aluminum (Al) and aluminum (Al) alloys. The first adhesive layer, disposed on the side of the stress-relieving layer that bonds the semiconductor device, comprises copper (Cu), tin (Sn), bismaleimide resin, and an organophosphorus compound represented by general formula (1) and / or an organosulfur compound represented by general formula (2); and The second adhesive layer, disposed on the side of the stress-relieving layer opposite to the side where the semiconductor device is bonded, comprises copper (Cu), tin (Sn), bismaleimide resin, and an organophosphorus compound represented by general formula (1) and / or an organosulfur compound represented by general formula (2).

[0012] R 1 -P(R 2 )-R 3 -P(R 4 )-R 5 ・・・(1) (In general formula (1), R) 1 R 2 R 3 R 4 R 5 Each of these groups independently represents an aromatic or aliphatic organic group containing carbon (C) and hydrogen (H), and its structure does not contain the following functional groups.

[0013] R 6 -SR 7 ・・・(2) (In general formula (2), R) 6 R 7 Each of these groups independently represents an aromatic or aliphatic organic group containing carbon (C) and hydrogen (H), and its structure does not contain the following functional groups.

[0014] [2] According to the conductive adhesive film of [1], the opening ratio formed by the through hole provided on the main surface of the metal foil is 30% or more.

[0015] [3] The conductive adhesive film according to [1] or [2], wherein the first adhesive layer and the second adhesive layer comprise an alloy containing copper (Cu) and nickel (Ni) and / or an alloy containing tin (Sn) and nickel (Ni), and in differential scanning calorimetry, has at least one endothermic peak in the temperature range of 100°C to 250°C, and does not have the above-mentioned endothermic peak after heating at 250°C for 5 minutes under a nitrogen atmosphere at atmospheric pressure.

[0016] [4] The conductive adhesive film according to [1] or [2], wherein the components of the first adhesive layer and / or the second adhesive layer permeate into the through hole.

[0017] [5] The conductive adhesive film according to [1] or [2], wherein the through holes are filled with a heat-resistant resin selected from the group consisting of polyimide resin, bismaleimide resin, polyamide resin, silicone resin, polyphenylene ether resin, polyphenylene sulfide resin and polyetherketone resin.

[0018] [6] The conductive adhesive film according to [1] or [2], wherein a first barrier layer is further provided between the stress relief layer and the first adhesive layer, the first barrier layer comprising at least one metal component selected from the group consisting of molybdenum (Mo), chromium (Cr), titanium (Ti), nickel (Ni) and tin (Sn), and a second barrier layer is further provided between the stress relief layer and the second adhesive layer, the second barrier layer comprising at least one metal component selected from the group consisting of molybdenum (Mo), chromium (Cr), titanium (Ti), nickel (Ni) and tin (Sn).

[0019] [7] The conductive adhesive film according to [1] or [2], wherein the melting point of the organophosphorus is above 60°C.

[0020] [8] The conductive adhesive film according to [1] or [2], wherein the organophosphine has a xanthene skeleton.

[0021] [9] The conductive adhesive film according to [1] or [2], wherein the melting point of the above-mentioned organic sulfide is above 60°C.

[0022]

[10] The conductive adhesive film according to [1] or [2], wherein the above-mentioned organic sulfide has an acryloyl group and / or a methacryloyl group and / or a vinyl ether group.

[0023]

[11] The conductive adhesive film according to [1] or [2], wherein the first adhesive layer and the second adhesive layer further comprise a compound represented by the following general formula (3).

[0024] Ar 1 -C(R 8 (R) 9 )-C(R 10 (R) 11 )-Ar 2 ・・・(3) (In general formula (3), Ar) 1 Ar 2 Each independently represents an aromatic group, R 8 R 9 R 10 R 11 Each group independently represents an aliphatic group.

[12] A method for joining dissimilar materials, wherein the conductive adhesive film described in [1] or [2] is used to perform pressureless sintering at 275°C or below for less than 10 minutes under a normal pressure nitrogen atmosphere, thereby joining dissimilar materials with different coefficients of linear expansion.

[0025]

[13] A semiconductor device structure wherein the semiconductor device is bonded to the first adhesive layer of the conductive adhesive film described in [1] or [2], and a substrate or lead frame is bonded to the second adhesive layer of the conductive adhesive film described in [1] or [2], thereby the semiconductor device is mounted on the substrate or lead frame.

[0026]

[14] A chip cutting bonding film, wherein a cutting tape is adhered to the second adhesive layer side of the conductive adhesive film described in [1] or [2] above.

[0027] In the above-described [1] method, the first adhesive layer is sintered by transient liquid phase sintering (TLPS) or the like, thereby bonding semiconductor devices such as power semiconductors to the stress relief layer via the sintered first adhesive layer. The second adhesive layer is sintered by transient liquid phase sintering (TLPS) or the like, thereby bonding components such as substrates and lead frames to the stress relief layer via the sintered second adhesive layer. In addition, in the above-described [1] method, a through hole is provided on the perforated metal foil constituting the stress relief layer, extending through the thickness direction of the metal foil. It should be noted that the "main surface" of the metal foil in the above-described [1] specifically refers to the side with the larger surface area among the outer surfaces of the metal foil, that is, the two surfaces used to divide and form the upper and lower edge edges with narrow surface areas. In addition, the “aperture ratio” in [2] above refers to [(the area of ​​all through holes provided on the main surface of the perforated metal foil constituting the stress relief layer) / (the area of ​​the main surface of the perforated metal foil constituting the stress relief layer + the area of ​​all through holes provided on the main surface of the perforated metal foil constituting the stress relief layer)] × 100 (unit %). In addition, in this invention, “atmospheric pressure” refers to atmospheric pressure.

[0028] Invention Effects According to the conductive adhesive film of the present invention, by providing a stress-relieving layer composed of a perforated metal foil, wherein the perforated metal foil has through holes on the main surface of the metal foil formed using at least one metal selected from the group consisting of copper (Cu), copper (Cu) alloys, aluminum (Al), and aluminum (Al) alloys, it exhibits excellent thermal conductivity and electrical conductivity. Furthermore, due to the stress-relieving properties and flexibility of the perforated metal foil, thermal fatigue and stress accumulation can be suppressed even if the thermal expansion coefficients of the semiconductor device and the component mounting the semiconductor device differ, thus preventing damage to the semiconductor device structure mounting the semiconductor device. In addition, according to the conductive adhesive film of the present invention, by providing a first adhesive layer and a second adhesive layer comprising copper (Cu), tin (Sn), bismaleimide resin, and an organophosphorus compound represented by the above general formula (1) and / or an organosulfur compound represented by the above general formula (2), a conductive adhesive film with excellent thermal fatigue resistance, sintering ease, and void prevention can be obtained without using expensive precious metals.

[0029] Furthermore, according to the conductive adhesive film of the present invention, the opening ratio formed by the through holes provided on the main surface of the perforated metal foil is 30% or more, thereby further improving the stress relief characteristics and flexibility of the perforated metal foil. Therefore, even if the thermal expansion rates of the semiconductor device and the component carrying the semiconductor device are different, thermal fatigue and stress accumulation can be suppressed, and damage to the semiconductor device structure carrying the semiconductor device can be prevented more reliably.

[0030] Furthermore, according to the conductive adhesive film of the present invention, the first adhesive layer and the second adhesive layer contain an alloy containing copper (Cu) and nickel (Ni) and / or an alloy containing tin (Sn) and nickel (Ni). In differential scanning calorimetry, the first adhesive layer and the second adhesive layer have at least one endothermic peak in the temperature range of 100°C to 250°C. Moreover, after heating at 250°C for 5 minutes under a nitrogen atmosphere at normal pressure, the above-mentioned endothermic peak is not present. Thus, the first adhesive layer and the second adhesive layer are sintered at normal pressure, low temperature and short time. Therefore, the ease of sintering is reliably improved.

[0031] Furthermore, according to the conductive adhesive film of the present invention, a first barrier layer is further provided between the stress relief layer and the first adhesive layer. The first barrier layer contains at least one metal component selected from the group consisting of molybdenum (Mo), chromium (Cr), titanium (Ti), nickel (Ni), and tin (Sn). A second barrier layer is further provided between the stress relief layer and the second adhesive layer. The second barrier layer contains at least one metal component selected from the group consisting of molybdenum (Mo), chromium (Cr), titanium (Ti), nickel (Ni), and tin (Sn). This prevents the metal component of the stress relief layer from diffusing into the first adhesive layer and the second adhesive layer. Therefore, it is possible to prevent the formation of copper and tin alloy phases from being hindered by the metal component of the stress relief layer, and the sintering ease is further improved.

[0032] Furthermore, according to the conductive adhesive film of the present invention, the first adhesive layer and the second adhesive layer further contain the compound represented by the above general formula (3), thereby the compound represented by the above general formula (3) acts as a curing agent for the bismaleimide resin, thus improving the heat resistance of the first adhesive layer and the second adhesive layer. In addition, the compound represented by the above general formula (3) is a non-oxide compound and does not interfere with the organophosphorus represented by the above general formula (1) and / or the organosulfur compound represented by the above general formula (2) as a reducing agent, thus preventing damage to the porosity. Attached Figure Description

[0033] Figure 1 This is a schematic cross-sectional view showing a general outline of the conductive adhesive film in one embodiment of the conductive adhesive film involved in the present invention.

[0034] Figure 2 This is a schematic cross-sectional view showing a general outline of the conductive adhesive film in another embodiment of the conductive adhesive film involved in the present invention.

[0035] Figure 3 This is a schematic cross-sectional view showing a general outline of the semiconductor device structure in one embodiment of the semiconductor device structure involved in the present invention.

[0036] Figure 4 This is a schematic cross-sectional view showing a schematic of the die-cutting bonding film in one embodiment of the die-cutting bonding film of the present invention. Detailed Implementation

[0037] The embodiments of the conductive adhesive film of the present invention, the bonding method of dissimilar materials using the conductive adhesive film, the semiconductor device structure having the conductive adhesive film, and the die-cutting bonding film having the conductive adhesive film will be described in detail below with reference to the accompanying drawings.

[0038] <Conductive adhesive film> like Figure 1 As shown, the conductive adhesive film 10 of the present invention is a conductive adhesive film for bonding semiconductor devices and components, comprising: a defined stress-relieving layer 1, a defined first adhesive layer 2 disposed on the side of the stress-relieving layer 1 where the semiconductor device is bonded, and a defined second adhesive layer 3 disposed on the side of the stress-relieving layer 1 opposite to the side where the semiconductor device is bonded. The stress-relieving layer 1 has a first main surface and a second main surface opposite to the first main surface. The first adhesive layer 2 is disposed on the side where the semiconductor device is bonded, i.e., the first main surface, and the second adhesive layer 3 is disposed on the side where the component is bonded, i.e., the second main surface.

[0039] The overall thickness of the conductive adhesive film of the present invention can be appropriately selected according to the usage conditions of the conductive adhesive film, but from the viewpoint of further mitigating the thermal stress generated between the semiconductor device and the component mounting the semiconductor device, its lower limit is preferably 10 μm, more preferably 30 μm, and particularly preferably 50 μm. On the other hand, from the viewpoint of preventing the increase of the thermal resistance of the conductive adhesive film and thereby improving the heat dissipation characteristics, the upper limit of the overall thickness of the conductive adhesive film is preferably 300 μm, more preferably 250 μm, and particularly preferably 200 μm.

[0040] (1) Stress relief layer The stress-relieving layer in the conductive adhesive film of the present invention is composed of a perforated metal foil, wherein through holes are provided on the main surface of the metal foil formed using at least one metal selected from the group consisting of copper (Cu), copper (Cu) alloys, aluminum (Al), and aluminum (Al) alloys. The stress-relieving layer is a layer that alleviates thermal stress generated between the semiconductor device and the component mounting the semiconductor device. In the conductive adhesive film of the present invention, by having the stress-relieving layer composed of the aforementioned perforated metal foil, excellent thermal conductivity and electrical conductivity are achieved. Furthermore, the perforated metal foil possesses stress-relieving characteristics and flexibility through the strain absorption effect of the through holes. Therefore, even if the thermal expansion rates of the semiconductor device and the component mounting the semiconductor device differ, thermal fatigue and stress accumulation can be suppressed, preventing damage to the semiconductor device structure.

[0041] As for the aforementioned perforated metal foil, any metal component having through holes provided on the main surface of the metal foil, and the metal foil being formed using at least one metal selected from the group consisting of copper (Cu), copper (Cu) alloys, aluminum (Al), and aluminum (Al) alloys, is not particularly limited. However, considering further improving the stress-relieving characteristics and flexibility of the perforated metal foil, so that even if the thermal expansion rates of the semiconductor device and the component carrying the semiconductor device are different, thermal fatigue and stress accumulation can be suppressed, thereby more reliably preventing damage to the semiconductor device structure carrying the semiconductor device, the aperture ratio obtained by the through holes provided on the main surface of the perforated metal foil is preferably 10% or more, more preferably 20% or more, and particularly preferably 30% or more. On the other hand, from the viewpoint of ensuring the electrical conductivity and thermal conductivity in the stress-relieving layer, the upper limit of the aperture ratio formed by the through holes provided on the main surface of the perforated metal foil is preferably 60%, and particularly preferably 50%. It should be noted that the number of through holes provided on the main surface of the perforated metal foil can be one or more.

[0042] The stress-relieving layer can be constructed from a single layer of perforated metal foil or from multiple layers of perforated metal foil. When using multiple layers of perforated metal foil to construct the stress-relieving layer, it can be constructed from perforated metal foil with the same aperture ratio or from perforated metal foil with different aperture ratios.

[0043] The thickness of the stress-relieving layer can be appropriately selected based on the usage conditions of the conductive adhesive film according to the present invention, but from the viewpoint of further mitigating the thermal stress generated between the semiconductor device and the component mounting the semiconductor device, its lower limit is preferably 5 μm, more preferably 20 μm, and particularly preferably 40 μm. On the other hand, from the viewpoint of preventing an increase in the thermal resistance of the conductive adhesive film of the present invention and improving heat dissipation characteristics, the upper limit of the thickness of the stress-relieving layer is preferably 250 μm, more preferably 200 μm, and particularly preferably 150 μm.

[0044] (2) First adhesive layer The first adhesive layer is disposed on the side of the stress relief layer that bonds the semiconductor device, and comprises copper (Cu), tin (Sn), bismaleimide resin, and an organophosphorus represented by the following general formula (1) and / or an organosulfur compound represented by the following general formula (2).

[0045] R 1 -P(R 2 )-R 3 -P(R 4 )-R 5 ・・・(1) (In general formula (1), R) 1 R 2 R 3 R 4R 5 Each of these groups independently represents an aromatic or aliphatic organic group containing carbon (C) and hydrogen (H), and its structure does not contain the following functional groups.

[0046] R 6 -SR 7 ・・・(2) (In general formula (2), R) 6 R 7 Each of these groups independently represents an aromatic or aliphatic organic group containing carbon (C) and hydrogen (H), and its structure does not contain the functional groups described below.

[0047] By heat-treating the conductive adhesive film of the present invention, copper (Cu) and tin (Sn) components in the first adhesive layer are sintered through a transient liquid phase sintering (TLPS) reaction, forming an alloy phase containing copper (Cu) and tin (Sn) in the sintered state (sintered state), resulting in an increased melting point. Furthermore, in this state of increased melting point of the first adhesive layer, a semiconductor device is bonded to the first adhesive layer. Therefore, even when the operating temperature of semiconductor devices such as power semiconductors is high, the bonding reliability between the first adhesive layer and the semiconductor device is excellent.

[0048] In the first adhesive layer, as metallic components, at least copper (Cu) and tin (Sn) are present, but no precious metals such as silver are present. Therefore, the first adhesive layer is an adhesive layer that does not contain expensive precious metals.

[0049] In the conductive adhesive film of the present invention, the organophosphorus represented by the following general formula (1) and the organosulfur compound represented by the following general formula (2) function as reducing agents.

[0050] R 1 -P(R 2 )-R 3 -P(R 4 )-R 5 ・・・(1) (In general formula (1), R) 1 R 2 R 3 R 4 R 5 Each of these groups independently represents an aromatic or aliphatic organic group containing carbon (C) and hydrogen (H), and its structure does not contain the following functional groups.

[0051] R 6 -SR 7 ・・・(2) (In general formula (2), R) 6 R 7 Each of these groups independently represents an aromatic or aliphatic organic group containing carbon (C) and hydrogen (H), and its structure does not contain the following functional groups.

[0052] If an oxide coating is formed on copper and tin, which are the metal components of the first bonding layer, the oxide coating hinders the sintering reaction, such as transient liquid phase sintering (TLPS), when the power semiconductor is bonded to components such as a substrate or lead frame by sintering. That is, it hinders the formation of the alloy phase containing copper and tin. The oxide coating is prevented from forming on copper and tin by reducing the oxide coating with organophosphorus compounds represented by general formula (1) and organosulfur compounds represented by general formula (2). Therefore, even if copper and tin, which are metal components that are more easily oxidized than noble metals, are used, the formation of an oxide coating on copper and tin can be prevented, the sintering reaction such as transient liquid phase sintering can be promoted, sintering can be made easier, and the formation of the alloy phase containing copper and tin can be promoted.

[0053] Neither the organophosphorus represented by general formula (1) nor the organosulfur compound represented by general formula (2) contains the following functional groups in their chemical structures. Therefore, when the organophosphorus represented by general formula (1) reduces the above-mentioned oxidized coating to organophosphorus oxide, and the organosulfur compound represented by general formula (2) reduces the above-mentioned oxidized coating to organosulfoxide, water molecules are not produced as byproducts.

[0054]

[0055] When the organophosphorus represented by general formula (1) undergoes a chemical change to organophosphorus oxide, and the organosulfide represented by general formula (2) undergoes a chemical change to organosulfoxide, water molecules, which are produced as byproducts, are not generated, thus preventing the formation of voids in the first adhesive layer in the sintered state. That is, the organophosphorus represented by general formula (1) and the organosulfide represented by general formula (2) exhibit excellent anti-void properties. As can be seen from the above, by including the organophosphorus represented by general formula (1) and / or the organosulfide represented by general formula (2) in the first adhesive layer, it is not necessary to perform pressure treatment on the semiconductor device structure on the substrate or the like to crush voids, thus preventing damage such as cracks from forming on the power semiconductor.

[0056] In the conductive adhesive film of the present invention, as a reducing agent, either an organophosphorus represented by general formula (1) or an organosulfur compound represented by general formula (2) can be used alone, or both an organophosphorus represented by general formula (1) and an organosulfur compound represented by general formula (2) can be used together.

[0057] The melting point of the organophosphorus represented by general formula (1) is not particularly limited, but from the perspective of storage stability, it is preferable that the organophosphorus maintains a fine crystalline state before being put into the semiconductor device mounting process, thereby suppressing the diffusion of the organophosphorus in the conductive adhesive film composition system and preventing premature reaction. At the same time, considering that when the organophosphorus is put into the semiconductor device mounting process and heating is started, the organophosphorus will rapidly begin to diffuse in the conductive adhesive film composition system and become a state in which the reaction can begin, the melting point of the organophosphorus is preferably 60°C or higher, and particularly preferably 80°C or higher.

[0058] Organophosphorus compounds represented by general formula (1) include, for example, organophosphorus compounds having a zeatin skeleton. Specifically, it is preferred that in general formula (1), R 1 R 2 R 4 R 5 They are aromatic groups and R, respectively. 3 Organophosphorus compounds having aromatic groups with a succinate skeleton; R is particularly preferred. 1 R 2 R 4 R 5 These are phenyl groups that can have substituents, and R. 3 It is an aromatic group having a succinate skeleton. Furthermore, as an organophosphorus represented by general formula (1), it is preferable that R in general formula (1) is... 1 R 2 R 4 R 5 They are aromatic groups and R, respectively. 3 Organophosphorus compounds with aliphatic groups; particularly preferred are R. 1 R 2 R 4 R 5 These are phenyl groups that can have substituents, and R. 3 It is an aliphatic group with 1 to 10 carbon atoms.

[0059] The melting point of the organosulfur compound represented by general formula (2) is not particularly limited, but from the perspective of storage stability, it is preferable that the organosulfur compound maintains a fine crystalline state before being put into the semiconductor device mounting process, thereby suppressing diffusion in the conductive adhesive film composition system and preventing premature reaction. At the same time, considering that when the organosulfur compound is put into the semiconductor device mounting process and heating is started, the organosulfur compound will rapidly begin to diffuse in the conductive adhesive film composition system and become a state in which the reaction can begin, the melting point of the organosulfur compound is preferably 60°C or higher, and particularly preferably 80°C or higher.

[0060] As an organosulfur compound represented by general formula (2), from the viewpoint that it can undergo a crosslinking reaction with the bismaleimide resin described later, thereby also contributing to improved heat fatigue resistance, organosulfur compounds having acryloyl and / or methacryloyl and / or vinyl ether groups are preferred, i.e., R 6 R 7 These are organic groups having an acryloyl group and / or a methacryloyl group and / or a vinyl ether group, with a particularly preferred organic group having an acryloyl group and / or a methacryloyl group. It should be noted that R 6 R 7 They can also be organic groups having aliphatic groups such as acryloyl and / or methacryloyl and / or vinyl ether groups, and aromatic groups such as phenyl groups.

[0061] In the conductive adhesive film of the present invention, a bismaleimide resin, which forms a polyimide crosslink with excellent heat resistance through thermosetting, is used as the thermosetting resin, based on the viewpoints of withstanding the high operating temperature of power semiconductors and preventing outgassing due to the absence of protic hydroxyl groups. Furthermore, because the bismaleimide resin has stress-relieving properties, the thermal fatigue resistance is improved in the sintered conductive adhesive film.

[0062] The amounts of the copper and tin-containing metal components, the reducing agent composed of an organophosphorus compound represented by general formula (1) and / or an organosulfur compound represented by general formula (2), and the bismaleimide resin in the first adhesive layer are not particularly limited. From the viewpoint of improving the bonding reliability of semiconductor devices by obtaining a sintered first adhesive layer, the lower limit of the amount of the copper and tin-containing metal components in 100% by mass of the first adhesive layer is preferably 60% by mass, more preferably 70% by mass, and particularly preferably 75% by mass. On the other hand, the upper limit of the amount of the copper and tin-containing metal components in 100% by mass of the first adhesive layer is preferably 95% by mass, more preferably 90% by mass, and particularly preferably 85% by mass.

[0063] From the viewpoint of improving sintering ease and void prevention, the lower limit of the amount of reducing agent composed of organophosphorus compounds represented by general formula (1) and / or organosulfur compounds represented by general formula (2) in 100% by mass of the first adhesive layer is preferably 0.1% by mass, more preferably 1.0% by mass, and particularly preferably 1.5% by mass. On the other hand, the upper limit of the amount of reducing agent composed of organophosphorus compounds represented by general formula (1) and / or organosulfur compounds represented by general formula (2) in 100% by mass of the first adhesive layer is preferably 20% by mass, more preferably 10% by mass, and particularly preferably 5% by mass.

[0064] From the viewpoint of reliably improving thermal fatigue resistance, the lower limit of the amount of bismaleimide resin in 100% by mass of the first adhesive layer is preferably 5% by mass, more preferably 10% by mass, and particularly preferably 15% by mass. On the other hand, the upper limit of the amount of bismaleimide resin in 100% by mass of the first adhesive layer is preferably 40% by mass, more preferably 35% by mass, and particularly preferably 30% by mass.

[0065] As can be seen from the above, in the conductive adhesive film of the present invention, by having a first adhesive layer containing copper, tin, bismaleimide resin, and organophosphorus represented by the above general formula (1) and / or organosulfur compound represented by the above general formula (2), a conductive adhesive film with excellent heat fatigue resistance, sintering ease and void prevention can be obtained without using expensive precious metals.

[0066] In the conductive adhesive film of the present invention, the metallic component of the first adhesive layer, in addition to copper and tin, may also contain nickel (Ni) as needed. That is, the metallic component may contain: an alloy containing copper (Cu) and nickel (Ni) and / or an alloy containing tin (Sn) and nickel (Ni). Nickel helps to promote the formation of the copper-tin alloy phase (intermetallic compound) during sintering, shortening the sintering reaction time.

[0067] Furthermore, when the first adhesive layer contains nickel (Ni) as an optional component, it is preferable that, in the differential scanning calorimetry (DSC) analysis, in the state before sintering (unsintered state), it has at least one endothermic peak in the temperature range of 100°C to 250°C, and after heating at 250°C for 5 minutes under a nitrogen atmosphere at atmospheric pressure, i.e., in the state after sintering (sintered state), it does not have the above-mentioned endothermic peak, and the above-mentioned endothermic peak disappears.

[0068] In the unsintered state, at least one endothermic peak observed within the aforementioned temperature range indicates the melting point of at least one metallic element constituting the metallic composition containing copper, tin, and nickel. This means that when the unsintered first adhesive layer is heated (sintered) within the aforementioned temperature range, a specific metallic component melts and spreads on the surface of the bonded material (power semiconductor), which is beneficial for the mounting of the power semiconductor at low temperatures. On the other hand, in the sintered state, no endothermic peak is observed within the aforementioned temperature range, meaning that the melting point of the metallic composition containing copper, tin, and nickel does not exist within this temperature range. This means that the molten metal, through intermetallic diffusion reactions, forms a copper- and tin-containing alloy phase (intermetallic compound) with a high melting point after sintering, resulting in excellent heat resistance.

[0069] After heating at 250°C for 5 minutes under a nitrogen atmosphere at atmospheric pressure, the aforementioned endothermic peak disappeared, indicating that the first adhesive layer was sintered at atmospheric pressure, low temperature, and short time. Therefore, the sintering ease of the first adhesive layer is reliably improved. In addition, the first adhesive layer can not only be sintered at low temperature (for mounting power semiconductors), but also exhibits excellent heat resistance after sintering (after mounting power semiconductors).

[0070] The amount of nickel in 100% by mass of the first adhesive layer is not particularly limited, but from the viewpoint of further improving the sintering reactivity of copper and tin, the lower limit is preferably 0.01% by mass, more preferably 0.02% by mass, and particularly preferably 0.05% by mass. On the other hand, the upper limit of the amount of nickel in 100% by mass of the first adhesive layer is preferably 20% by mass, more preferably 15% by mass, and particularly preferably 10% by mass.

[0071] In addition, the first adhesive layer of the conductive adhesive film of the present invention may further contain a compound represented by the following general formula (3) as needed.

[0072] Ar 1 -C(R 8 (R) 9 )-C(R 10 (R) 11 )-Ar 2 ・・・(3) (In general formula (3), Ar) 1 Ar 2 Each independently represents an aromatic group, R 8 R 9 R 10 R 11 Each group independently represents an aliphatic group. The compound represented by the above general formula (3) is a thermal free radical initiator, which acts as a curing agent for bismaleimide resin, thus improving the heat resistance and thermal fatigue resistance of the first adhesive layer. In addition, the compound represented by the above general formula (3) is a non-oxide compound, which will not interfere with the organophosphorus represented by the above general formula (1) and / or the organosulfur compound represented by the above general formula (2) as a reducing agent, thus preventing damage to the porosity of the first adhesive layer.

[0073] In general formula (3), Ar is preferred. 1 Ar 2 These are phenyl groups that can have substituents, and R. 8 R 9 R 10 R 11 Each group is an aliphatic group having 1 to 10 carbon atoms, with Ar being particularly preferred. 1 Ar 2They are phenyl and R, respectively. 8 R 9 R 10 R 11 Each is an aliphatic group with 1 to 5 carbon atoms.

[0074] The amount of the compound represented by general formula (3) in 100% by mass of the first adhesive layer is not particularly limited. From the viewpoint of further improving the heat resistance and thermal fatigue resistance of the first adhesive layer, the lower limit is preferably 0.01% by mass, more preferably 0.05% by mass, and particularly preferably 0.1% by mass. On the other hand, the upper limit of the amount of the compound represented by general formula (3) in 100% by mass of the first adhesive layer is preferably 2% by mass, more preferably 1% by mass, and particularly preferably 0.5% by mass.

[0075] The thickness of the first adhesive layer can be appropriately selected according to the usage conditions of the conductive adhesive film according to the present invention. From the viewpoint of reliably obtaining the bonding reliability between the semiconductor device and the stress relief layer, its lower limit is preferably 1 μm, more preferably 4 μm, and particularly preferably 8 μm. On the other hand, from the viewpoint of preventing the thermal resistance of the conductive adhesive film from increasing, thereby improving the heat dissipation characteristics, the upper limit of the thickness of the first adhesive layer is preferably 50 μm, more preferably 40 μm, and particularly preferably 30 μm.

[0076] Components of the first or second adhesive layer can also permeate into the through-holes of the perforated metal foil constituting the stress-relieving layer. Alternatively, components of the first or second adhesive layer can be filled into the through-holes of the perforated metal foil constituting the stress-relieving layer. By permeating the adhesive layer components into the through-holes of the perforated metal foil, peeling between the stress-relieving layer and the adhesive layer can be prevented. Filling the through-holes of the perforated metal foil with components of the second adhesive layer further reliably prevents peeling between the stress-relieving layer and the second adhesive layer. Furthermore, a heat-resistant resin with a different composition than the first and second adhesive layers can be filled into the through-holes of the perforated metal foil constituting the stress-relieving layer. In this case, for example, polyimide resin, bismaleimide resin, polyamide resin, silicone resin, polyphenylene ether resin, polyphenylene sulfide resin, polyetherketone resin, etc., can be used. By filling the through-holes of the stress-relieving layer with a heat-resistant resin, further stress-relieving capabilities can be imparted. In these heat-resistant resins, from the viewpoint of affinity with the components of the adhesive layer, it is particularly preferable to fill the through-holes with bismaleimide resin, thereby making the adhesion between the adhesive layer and the resin filling the through-holes stronger.

[0077] (3) Second adhesive layer The second adhesive layer is disposed on the side of the stress relief layer opposite to the side where the semiconductor device is bonded. For example, the second adhesive layer is disposed on the side of the stress relief layer where components such as lead frames or substrates are bonded.

[0078] The second adhesive layer has the same composition as the first adhesive layer described above. That is, the second adhesive layer contains copper (Cu), tin (Sn), bismaleimide resin, and organophosphorus compounds represented by the following general formula (1) and / or organosulfur compounds represented by the following general formula (2).

[0079] R 1 -P(R 2 )-R 3 -P(R 4 )-R 5 ・・・(1) (In general formula (1), R) 1 R 2 R 3 R 4 R 5 Each of these groups independently represents an aromatic or aliphatic organic group containing carbon (C) and hydrogen (H), and its structure does not contain the following functional groups. R 6 -SR 7 ・・・(2) (In general formula (2), R) 6 R 7 Each of these groups independently represents an aromatic or aliphatic organic group containing carbon (C) and hydrogen (H), and its structure does not contain the following functional groups. Like the first adhesive layer, the second adhesive layer may also contain nickel (Ni) as a metallic component in addition to copper and tin, as needed. Furthermore, like the first adhesive layer, the second adhesive layer may also contain a compound represented by the following general formula (3), as needed.

[0080] Ar 1 -C(R 8 (R) 9 )-C(R 10 (R) 11 )-Ar 2 ・・・(3) (In general formula (3), Ar) 1 Ar 2 Each independently represents an aromatic group, R 8 R 9 R 10 R 11 Each group independently represents an aliphatic group. Since the second adhesive layer has the same composition as the first adhesive layer described above, detailed descriptions of each component and its effects are omitted here.

[0081] The thickness of the second adhesive layer can be appropriately selected according to the usage conditions of the conductive adhesive film according to the present invention, but from the viewpoint of reliably obtaining the bonding reliability between the lead frame or substrate and the stress relief layer, its lower limit is preferably 1 μm, more preferably 4 μm, and particularly preferably 8 μm. On the other hand, from the viewpoint of preventing the thermal resistance of the conductive adhesive film from increasing, thereby improving the heat dissipation characteristics, the upper limit of the thickness of the first adhesive layer is preferably 50 μm, more preferably 40 μm, and particularly preferably 30 μm.

[0082] The components of the second adhesive layer can also seep into the through-holes of the perforated metal foil constituting the stress-relieving layer. Alternatively, the components of the second adhesive layer can be filled into the through-holes of the perforated metal foil constituting the stress-relieving layer. By allowing the components of the second adhesive layer to seep into the through-holes of the perforated metal foil, peeling between the stress-relieving layer and the second adhesive layer can be prevented. Furthermore, by filling the through-holes of the perforated metal foil with the components of the second adhesive layer, peeling between the stress-relieving layer and the second adhesive layer can be prevented more reliably.

[0083] (4) First barrier layer like Figure 2 As shown, in the conductive adhesive film 10 of the present invention, a first barrier layer 4 may be further provided between the stress relief layer 1 and the first adhesive layer 2 as needed. The first barrier layer 4 contains at least one metal component selected from the group consisting of molybdenum (Mo), chromium (Cr), titanium (Ti), nickel (Ni) and tin (Sn).

[0084] By further providing a first barrier layer 4 between the stress relief layer 1 and the first adhesive layer 2, the metallic components of the stress relief layer 1 can be prevented from diffusing into the first adhesive layer 2. Therefore, the formation of the copper and tin alloy phase in the first adhesive layer 2 can be prevented from being hindered by the metallic components of the stress relief layer 1. As a result, the sintering ease of the first adhesive layer 2 is further improved.

[0085] (5) Second barrier layer like Figure 2 As shown, in the conductive adhesive film 10 of the present invention, a second barrier layer 5 may be further provided between the stress relief layer 1 and the second adhesive layer 3 as needed. The second barrier layer 5 contains at least one metal component selected from the group consisting of molybdenum (Mo), chromium (Cr), titanium (Ti), nickel (Ni) and tin (Sn).

[0086] By further providing a second barrier layer 5 between the stress relief layer 1 and the second adhesive layer 3, the metallic components of the stress relief layer 1 can be prevented from diffusing into the second adhesive layer 3. Therefore, the formation of the copper and tin alloy phase in the second adhesive layer 3 can be prevented from being hindered by the metallic components of the stress relief layer 1. As a result, the sintering ease of the second adhesive layer 3 is further improved.

[0087] <Method for manufacturing conductive adhesive films> The following describes an example of a method for manufacturing the conductive adhesive film of the present invention. First, the components constituting the first adhesive layer and the second adhesive layer are dissolved in an organic solvent such as toluene to prepare a conductive composition constituting the first adhesive layer and the second adhesive layer. Then, the prepared conductive composition is coated onto both sides of a perforated metal foil forming a stress-relieving layer at a desired thickness. The coating method is not particularly limited, and known coating methods can be used, such as comma coaters, screen printing, bar coaters, applicators, blade coaters, knife coaters, roll coaters, and gravure coaters. After coating the conductive composition, a first adhesive layer is formed on the first main surface of the stress relief layer, which is used for bonding semiconductor devices, by drying at 100°C to 150°C for 1 minute to 30 minutes, and a second adhesive layer is formed on the second main surface, which is used for bonding components.

[0088] It should be noted that, when a first barrier layer and a second barrier layer are further provided, before coating the conductive composition on the perforated metal foil, a first barrier layer and a second barrier layer are formed on both sides of the perforated metal foil by sputtering or the like, and the conductive composition is coated on the formed first barrier layer and the second barrier layer.

[0089] As described above, the conductive adhesive film of the present invention can bond components with different coefficients of thermal expansion while suppressing thermal fatigue and stress accumulation. Therefore, it is possible to bond dissimilar materials with different coefficients of linear expansion using the conductive adhesive film of the present invention. Furthermore, as described above, in the conductive adhesive film of the present invention, the first adhesive layer and the second adhesive layer are sintered at normal pressure, low temperature, and for a short time. Therefore, it is possible to bond dissimilar materials with different coefficients of linear expansion under simple sintering conditions.

[0090] First, components with different coefficients of thermal expansion are prepared, such as a SiC power semiconductor and a lead frame or substrate for mounting the SiC power semiconductor. Next, a structure is formed in which the conductive adhesive film of the present invention is sandwiched between the SiC power semiconductor and the lead frame or substrate. Next, the formed structure is heat-treated at atmospheric pressure and an inert gas atmosphere (e.g., nitrogen) at a temperature below 275°C for less than 10 minutes. Through the above-described heat treatment (i.e., pressureless sintering), the first adhesive layer and the second adhesive layer are sintered, enabling the bonding of dissimilar materials (SiC power semiconductor and lead frame or substrate) with different coefficients of thermal expansion.

[0091] It should be noted that the lower limit of the heating temperature for the above-mentioned heat treatment is, for example, 230°C, preferably 250°C. Furthermore, the lower limit of the heating time for the above-mentioned heat treatment is, for example, 3 minutes, preferably 5 minutes.

[0092] <Semiconductor Device Structure> like Figure 3 As shown, the semiconductor device structure 100 of the present invention has a structure in which a semiconductor device 20, such as a SiC power semiconductor, is mounted on a component such as a substrate or a lead frame 30. In such a structure, the semiconductor device 20 is bonded to a first adhesive layer of the conductive adhesive film 10 of the present invention, and the substrate or lead frame 30 is bonded to a second adhesive layer of the conductive adhesive film 10 of the present invention.

[0093] As described above, the semiconductor device structure of the present invention has a structure that mounts semiconductor devices such as SiC power semiconductors onto components such as substrates or lead frames via the conductive adhesive film of the present invention. Furthermore, in the semiconductor device structure of the present invention, the conductive adhesive film of the present invention functions to bond semiconductor devices such as SiC power semiconductors onto components such as substrates or lead frames.

[0094] The semiconductor device structure of the present invention can be manufactured, for example, by placing a semiconductor device such as a SiC power semiconductor on the surface of a component such as a substrate or lead frame via the conductive adhesive film of the present invention, and performing a heat treatment (e.g., reflow soldering) for less than 10 minutes at a temperature of 275°C or below under normal pressure and an inert gas (e.g., nitrogen) atmosphere.

[0095] It should be noted that the lower limit of the heating temperature for the above-mentioned heat treatment is, for example, 230°C, preferably 250°C. Furthermore, the lower limit of the heating time for the above-mentioned heat treatment is, for example, 3 minutes, preferably 5 minutes.

[0096] <Cutting Chip Bonding Film> like Figure 4As shown, the chip dicing bonding film 200 of the present invention has a structure in which a dicing tape 40 is adhered to the second adhesive layer side of the conductive adhesive film 10 of the present invention. The chip dicing bonding film 200 of the present invention is a structure formed by integrating the conductive adhesive film 10 and the dicing tape 40 of the present invention.

[0097] By attaching a semiconductor wafer to the first adhesive layer of the conductive adhesive film of the present invention, the semiconductor wafer can be attached to the dicing tape via the conductive adhesive film of the present invention. Because the dicing chip bonding film of the present invention can attach the semiconductor wafer to the dicing tape via the conductive adhesive film of the present invention, it can prevent the semiconductor chip from scattering when dicing the semiconductor wafer to a specified size for manufacturing semiconductor chips.

[0098] Example Next, embodiments of the present invention will be described. The present invention is not limited to these embodiments as long as it does not depart from its spirit. Additionally, room temperature refers to the range of 25°C ± 5°C.

[0099] Manufacturing of conductive adhesive films of Examples 1-9 and Comparative Examples 1-4 The components shown in Tables 1-3 below were dissolved in 100 ml of toluene according to the proportions shown in Tables 1-3 below to prepare the conductive compositions constituting the first and second adhesive layers used in Examples 1-9 and Comparative Examples 1-4. Subsequently, the prepared conductive compositions were coated onto both sides of the metal foil constituting the stress-relieving layers shown in Tables 1-3 below using a comma coater, and dried at 130°C for 3 minutes to form a first adhesive layer on the first main surface of the stress-relieving layer and a second adhesive layer on the second main surface, thus preparing the conductive adhesive films of Examples 1-9 and Comparative Examples 2-4. It should be noted that in Comparative Example 1, the conductive adhesive film was prepared by directly bonding the first and second adhesive layers. Furthermore, for the perforated metal foil used in Examples 8 and 9, a perforated metal foil in which bismaleimide resin was pre-filled in the through-holes before the adhesive layer coating was applied.

[0100] For the first and second barrier layers in Examples 6, 7, and 9, before the conductive composition is coated onto the metal film constituting the stress relief layer, the first and second barrier layers are formed by sputtering on both sides of the perforated metal foil constituting the stress relief layer, and the conductive composition is coated onto the formed first and second barrier layers using a comma coater.

[0101] On the conductive adhesive film prepared as described above, a cutting tape with an acrylic adhesive is bonded to a polyolefin substrate to obtain the chip cutting bonding films of Examples 1-9 and Comparative Examples 1-4.

[0102] The detailed information for each component in Tables 1 to 3 below is as follows.

[0103] • NOFMER BC (non-oxide): 2,3-dimethyl-2,3-diphenylbutane, curing agent for bismaleimide resins, Nippon Oil Co., Ltd.

[0104] Installation procedure Using the die bonding films of Examples 1-9 and Comparative Examples 1-4, 0.2 mm thick SiC chips treated with Ag metallization were bonded at 70°C and then cut to a size of 5 mm × 5 mm to obtain SiC chips with conductive adhesive films. The obtained SiC chips with conductive adhesive films were picked up using a pick-up die bonder and mounted on an active copper circuit board (AMC substrate) with Cu as the outermost surface at 90°C for 2 seconds. Subsequently, the chip-mounted samples were installed in a reflow oven under a nitrogen atmosphere at atmospheric pressure, at the sintering temperatures and times listed in Tables 1-3, to obtain the mounted samples of Examples 1-9 and Comparative Examples 1-4.

[0105] The evaluation and measurement items are as follows.

[0106] (1) Thermal fatigue resistance 1 For the installation samples of Examples 1 to 9 and Comparative Examples 1 to 4, a thermal shock test (TCT) was conducted, with 500 cycles in a temperature range of -45°C to 200°C. For the installed samples after the test, the peeling state of the SiC chip was visually observed and evaluated according to the following criteria. An evaluation of △ or above was considered acceptable.

[0107] ○: No peeling △: Partial peeling ×: Peeling occurs across the entire surface. (2) Heat fatigue resistance 2 For the installation samples of Examples 1 to 9 and Comparative Examples 1 to 4, as a thermal shock test (TCT), 1000 cycles were performed in a temperature range of -45°C to 230°C. For the installation samples after treatment, the peeling state of the SiC chip was visually observed and evaluated according to the following criteria. An evaluation of △ or above is considered qualified.

[0108] ○: No peeling △: Partial peeling ×: Peeling occurs across the entire surface. (3) Shortest sintering time Conductive adhesive films were collected from the installation samples of Examples 1-9, weighed in doses of 10 mg, and sealed in a special aluminum dish for testing. A high-sensitivity differential scanning calorimeter (DSC7000X, Hitachi High-Tech Science) was used under a nitrogen atmosphere (nitrogen flow rate 20 mL / min) at a heating rate of 5 °C / min over a temperature range of room temperature to 350 °C. Based on the obtained DSC spectra, the shortest sintering time at which the endothermic peak in the 200 °C–250 °C temperature region was confirmed to have disappeared was determined.

[0109] For the installation samples of Comparative Examples 1 to 3, the sintering temperature of the installation process was 350°C. For the installation sample of Comparative Example 4, the sintering temperature of the installation process was 350°C, and pressure was applied with a 250g tungsten hammer. Otherwise, the process was carried out in the same manner as in Examples 1 to 9, and the shortest sintering time at which the endothermic peak disappeared was confirmed.

[0110] (4) Porosity in sintered state For the installation samples of Examples 1-9 and Comparative Examples 1-4, non-destructive internal inspection was performed using ultrasonic testing (SAT) to detect the void generation rate (%) of the first and second adhesive layers in the sintered state. It should be noted that only for the installation sample of Comparative Example 4, pressure was applied using a tungsten hammer during the installation process. Furthermore, the void generation rate in the sintered state was evaluated according to the following criteria.

[0111] ◎: Less than 3% 〇: 3% or more but less than 5% ×: Greater than 5% (5) Reflow soldering workability The following criteria are used to evaluate reflow soldering workability: Under normal pressure and with a minimum sintering time of 10 minutes, if the void generation rate in the sintered state is rated "○" or higher after reflow soldering, and the temperature shock test (TCT) of 500 cycles within a temperature range of -45℃ to 200℃ is rated "△" or higher, then the workability is rated "◎ Very Good"; Even with a minimum sintering time exceeding 10 minutes under normal pressure, if the void generation rate in the sintered state is "○" after reflow soldering, then the workability is rated "◎ Very Good". If the above conditions are met, and the thermal shock test (TCT) of 500 cycles in the temperature range of -45℃ to 200℃ is rated "△" or above, the condition is rated "○ Good". If any one of the following conditions is not met, the condition is rated "× Poor".

[0112] The composition and evaluation results of the conductive adhesive films of Examples 1 to 9 are shown in Tables 1 to 2 below, and the composition and evaluation results of the conductive adhesive films of Comparative Examples 1 to 4 are shown in Table 3 below.

[0113] [Table 1]

[0114] [Table 2]

[0115] [Table 3]

[0116] As shown in Tables 1 and 2, in Examples 1 to 9, which contain an organophosphorus compound represented by general formula (1) or an organosulfur compound represented by general formula (2) in the first and second adhesive layers, the shortest sintering time of 5 to 30 minutes is achieved at 270°C and atmospheric pressure, with excellent sintering ease and a void generation rate of less than 5% in the sintered state, resulting in excellent void prevention. Furthermore, in Examples 2 to 9, which use a perforated metal foil with an opening ratio of 30% as a stress-relieving layer, excellent thermal fatigue resistance 1 and thermal fatigue resistance 2 are also observed.

[0117] On the other hand, in Comparative Examples 1 to 4, which do not contain organophosphorus compounds represented by general formula (1) or organosulfur compounds represented by general formula (2) in the first and second adhesive layers, void prevention cannot be obtained in Comparative Examples 1 to 3 during the installation process under normal pressure, while in Comparative Example 4, pressure treatment is required during the installation process in order to obtain void prevention.

[0118] Symbol Explanation 1 Stress-relieving layer; 2 First adhesive layer; 3 Second adhesive layer; 4 First barrier layer; 5 Second barrier layer; 10 Conductive adhesive film; 20 Semiconductor device; 30 Substrate (lead frame); 40 Cutting tape; 100 Semiconductor device structure; 200 Cutting chip bonding film.

Claims

1. A conductive adhesive film for bonding semiconductor devices and components, and comprising: A stress-relieving layer is composed of a perforated metal foil, wherein the perforated metal foil has through holes on the main surface of the metal foil formed of at least one metal selected from the group consisting of copper (Cu), copper (Cu) alloys, aluminum (Al) and aluminum (Al) alloys. A first adhesive layer, disposed on the side of the stress-relieving layer for bonding the semiconductor device, comprises copper (Cu), tin (Sn), bismaleimide resin, and an organophosphorus compound represented by general formula (1) and / or an organosulfur compound represented by general formula (2); and The second adhesive layer, disposed on the side of the stress-relieving layer opposite to the side for bonding the semiconductor device, comprises copper (Cu), tin (Sn), bismaleimide resin, and an organophosphorus compound represented by general formula (1) and / or an organosulfur compound represented by general formula (2). R 1 -P(R 2 )-R 3 -P(R 4 )-R 5 ・・・(1) In general formula (1), R 1 R 2 R 3 R 4 R 5 Each of these groups independently represents an aromatic or aliphatic organic group containing carbon (C) and hydrogen (H), and its structure does not contain the following functional groups. R 6 -S-R 7 ・・・(2) In general formula (2), R 6 R 7 Each of these groups independently represents an aromatic or aliphatic organic group containing carbon (C) and hydrogen (H), and its structure does not contain the following functional groups. 。 2. The conductive adhesive film according to claim 1, wherein, The opening ratio formed by the through holes provided on the main surface of the metal foil is 30% or more.

3. The conductive adhesive film according to claim 1 or 2, wherein, The first adhesive layer and the second adhesive layer comprise an alloy containing copper (Cu) and nickel (Ni) and / or an alloy containing tin (Sn) and nickel (Ni), and have at least one endothermic peak in the temperature range of 100°C to 250°C in differential scanning calorimetry, and do not have the said endothermic peak after heating at 250°C for 5 minutes under a nitrogen atmosphere at atmospheric pressure.

4. The conductive adhesive film according to claim 1 or 2, wherein, Components of the first adhesive layer and / or the second adhesive layer seep into the through hole.

5. The conductive adhesive film according to claim 1 or 2, wherein, The through hole is filled with a heat-resistant resin selected from the group consisting of polyimide resin, bismaleimide resin, polyamide resin, silicone resin, polyphenylene ether resin, polyphenylene sulfide resin and polyetherketone resin.

6. The conductive adhesive film according to claim 1 or 2, wherein, A first barrier layer is further disposed between the stress-relieving layer and the first adhesive layer. The first barrier layer contains at least one metal component selected from the group consisting of molybdenum (Mo), chromium (Cr), titanium (Ti), nickel (Ni), and tin (Sn). A second barrier layer is further disposed between the stress-relieving layer and the second adhesive layer. The second barrier layer contains at least one metal component selected from the group consisting of molybdenum (Mo), chromium (Cr), titanium (Ti), nickel (Ni), and tin (Sn).

7. The conductive adhesive film according to claim 1 or 2, wherein, The organophosphine has a melting point above 60°C.

8. The conductive adhesive film according to claim 1 or 2, wherein, The organophosphorus has a zeatin skeleton.

9. The conductive adhesive film according to claim 1 or 2, wherein, The organic sulfide has a melting point of 60°C or higher.

10. The conductive adhesive film according to claim 1 or 2, wherein, The organosulfur compound has an acryloyl group and / or a methacryloyl group and / or a vinyl ether group.

11. The conductive adhesive film according to claim 1 or 2, wherein, The first adhesive layer and the second adhesive layer further comprise a compound represented by the following general formula (3). Ar 1 -C(R 8 )(R 9 )-C(R 10 )(R 11 )-Ar 2 ・・・(3) In general formula (3), Ar 1 Ar 2 Each independently represents an aromatic group, R 8 R 9 R 10 R 11 Each group independently represents an aliphatic group.

12. A method for joining dissimilar materials, wherein, Using the conductive adhesive film as described in claim 1 or 2, pressureless sintering for less than 10 minutes at 275°C under normal nitrogen atmosphere is performed, thereby bonding dissimilar materials with different coefficients of linear expansion.

13. A semiconductor device structure obtained by mounting a semiconductor device on a substrate or lead frame, wherein, The semiconductor device is bonded to the first adhesive layer of the conductive adhesive film according to claim 1 or 2, and the substrate or lead frame is bonded to the second adhesive layer of the conductive adhesive film according to claim 1 or 2.

14. A chip-cutting bonding film, wherein, Cutting tape is adhered to the second adhesive layer side of the conductive adhesive film according to claim 1 or 2.

Citation Information

Patent Citations

  • Bonding member for semiconductor devices

    JP2022050871A